Controversial around Tax and Taxation System - Danuta Mliczewska (Contemporary Economics)
The topic of the analysis is concepts of a tax and taxation systems, which are used by the representatives of various scientific disciplines, above others finance, economics and tax law. Contrary to those using the above terminology referring to taxes and taxation systems, neither taxes nor taxation systems are, despite appearances, univocal and explicit concepts. The analysis presents the chosen definitions of taxes and taxation systems, across which we can come on the grounds of the disciplines mentioned above: finance, tax law and economics as well as the authorís of the analysis comments on the concepts.